Beyond Genius and Insanity: Investigating the Psychopathic Obsessions of Grenouille in Patrick Süskind’s Perfume - Bassem KAABECHE.Fadila BENGUESMIA, Dr Mohammed SENOUSSI (UNIVERSITY OF MOHAMED BOUDIAF, 2022)
ABSTRACT This study addresses the issue and portrayal of psychopathy in Patrick Süskind's Perfume: the story of a murderer. This research, entitled Beyond Genius and Insanity: Investigating the Psychopathic Obsessions of Grenouille in Patrick Süskind's Perfume, seeks to examine the layers of meaning behind the ceaseless bloodstained murders of the protagonist, Jean-Baptiste Grenouille, in eighteenth-century France. Likewise, the study strives to underscore genius and inborn talent as a powerful impetus that led to the protagonist's transformative self-quest of manipulation, solitude, power and self-destruction. As a result, this research ascertains that the protagonist Jean-Baptiste Grenouille exhibits behavioural patterns that correspond to and overlap with the psychopath checklist. It also unveils the genius yet villainous archetypal nature of this latter, who is trapped in the fate between individuation and self-destruction
Keywords: Key Words: Perfume, Süskind, Psychopathy, Manipulation,Evil, Genius, Power, Archetype, Identity Crisis.